PENGARUH PERSEPSI TEKNOLOGI DAN KEMUDAHAN PELAYANAN TERHADAP MINAT NASABAH MENGGUNAKAN MOBILE BANKING DENGAN SIKAP PENGGUNAAN SEBAGAI VARIABEL INTERVENING (STUDI PT BANK BSI KCP LOMBOK AIKMEL) - Riswandi riswandi; Muh. Baihaqi; Tati Atmayanti (Universitas Islam Negeri Mataram, 2023)
This study aims to determine the effect of Perceptions of Technology and Ease of Service on Customer Interests in Using Mobile Banking with Attitudes to Use as Intervening Variables (Study at PT Bank BSI KCP Lombok Aikmel). This research is a quantitative research with the type of causal associative research. The data collection technique in this study used a probability sampling technique with a simple random sampling method with a sample size of 100 respondents. The data analysis technique used in this study is multiple linear regression analysis with the development of a path analysis model with the help of the SPSS 26 program. In this study, two types of models were used, namely the first model and the second model. Based on the research results obtained in model I (first) that the variable Perception of Technology and Ease of Service has a significant effect on the Attitude of Use variable. While the results of the research on model II (second) found that the variables Perception of Technology and Ease of Service have a significant effect on Customer Interests in Using Mobile Banking with Attitudes of Use as intervening variables.